Redécouvrir Athènes. Balades urbaines et récits quotidiens du centre-ville - Dimitra Kanellopoulou (Bulletin de l’Association de Géographes Français)
Since the 1980s, extended pedestrianization works in Athens’ public spaces have been designed to sharpen the tourist and cultural profile of the city, resulting in a lively return to walking as a leisure activity within the historic center. There are many associations of inhabitants, who were created especially after the 2000s, offering the rediscovery of the city through collective walks. Based on a field survey, interviews with local actors and the founders and participants of the Atenistas group, the article questions the emergence of a new form of urban walk that juggles between tourist practice and sociability and citizen’s action. Walking together and discussing the common experience of walking, confronts the inhabitants and participants with the Atenistas group’s walk-events, with various urban narratives hitherto unknown or marginalized. It is the objective of this article to question the conditions of creation and gradual emergence of a new form of urban practice that seeks to respond to issues of tourist and economic reactivation of the city center with a focus on the renewal of the social bond: by walking, meeting, discovering.